THE IMPACT OF GEOMAGNETIC STORMS ON PATIENTS WITH HYPERTENSION - Kamalova Sayyora (Web of Journals Publishing, 2025)
This article explores the influence of geomagnetic storms on individuals diagnosed with hypertension. Geomagnetic storms, which are caused by solar activity, have been found to affect the Earth's magnetic field and may have significant physiological effects on the human cardiovascular system. This paper reviews current research findings that link space weather phenomena to blood pressure fluctuations, increased hospital admissions, and cardiovascular incidents in hypertensive patients. Understanding these effects can lead to improved clinical management during periods of high geomagnetic activity.
Keywords: Geomagnetic storms, Hypertension, Cardiovascular health, Space weather, Blood pressure.